Concern for others leads to vicarious optimism - Kappes, A; Faber, N; Kahane, G; Savulescu, J; Crockett, M (SAGE Publications, 2018)
An optimistic learning bias leads people to update their beliefs in response to better-than-expected “good news”, but neglect worse-than-expected “bad news”. Because evidence suggests this bias arises from self-concern, we hypothesized that a similar bias may affect beliefs about others’ future, to the extent that people care about others. Here, we demonstrate the phenomenon of vicarious optimism and show that it arises from concern for others. Participants predicted the likelihood of unpleasant future events that could happen to either themselves or others. In addition to showing an optimistic learning bias for events affecting themselves, people showed vicarious optimism when learning about events affecting friends and strangers. Vicarious optimism for strangers correlated with generosity toward strangers, and experimentally increasing concern for strangers amplified vicarious optimism for them. These findings suggest that concern for others can bias beliefs about their future welfare and that optimism in learning is not restricted to oneself.